1978
DOI: 10.1149/1.2131545
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Properties of Thin Tunnelable SiO2 Films Using a Vaporized  O 2 Source at Liquid  N 2 Temperature

Abstract: A high temperature (700~176 oxidation process for the formation of thin tunnelable SiO2 (20-70A) is described. This oxidation process uses liquid 02 at liquid N2 temperature as a source of oxidant and oxygen is vaporized just before the furnace tube to supply a water-free oxidant ambient. The activation energy (20.2 keal/mole) of oxidation rate differs from that previous (43.9 kcal/mole) which has been evaluated for thin oxide growth using the 02/N2 partial pressure method. By the use of this technique we can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

1980
1980
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
0
10
2
Order By: Relevance
“…However, Fehlner (22) reported that the Cabrera-Mott model (23) (CM model) is valid for explaining the oxidation under low temperature or low pressure conditions. Kamigaki et al (24) and Horiuchi et al (25) reported that the CM model rather than the DG model was adequate for explaining the kinetics of thermal oxidation under low partial pressures, in which diluted oxygen is used to grow very thin oxide films of less than 10 nm for MNOS nonvolatile memory devices. Furthermore, Yamasaki et al…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Fehlner (22) reported that the Cabrera-Mott model (23) (CM model) is valid for explaining the oxidation under low temperature or low pressure conditions. Kamigaki et al (24) and Horiuchi et al (25) reported that the CM model rather than the DG model was adequate for explaining the kinetics of thermal oxidation under low partial pressures, in which diluted oxygen is used to grow very thin oxide films of less than 10 nm for MNOS nonvolatile memory devices. Furthermore, Yamasaki et al…”
Section: Resultsmentioning
confidence: 99%
“…[3] rather than Eq. [5], since the oxide thickness is much larger than the results obtained from Kamigaki et al (24) and Horiuchi et al (25). The oxidation rate, i.e., dx/dt at an arbitrary oxide thickness, can be estimated by differentiating Eq.…”
Section: Table I Values Of T Ii(b/a) and I/b From The Deal-grove Ther...mentioning
confidence: 99%
“…There is, however, a maximum thickness at which the Mott-Cabrera mechanism stops being effective. Horiuchi (20) shows that this thickness is about 60-70A which is much less than the 200-800A oxide thickness where the rapid initial growth is found (19).…”
Section: Xos--ko2t+kh2o[ T+~exp(--+)--t]mentioning
confidence: 86%
“…It was shown by Horiuchi et al (20) that for extremely dry oxygen ambients an inverse logarithmic growth regime is found which is characteristic for the field-assisted growth (also called Mott-Cabrera mechanism). There is, however, a maximum thickness at which the Mott-Cabrera mechanism stops being effective.…”
Section: Xos--ko2t+kh2o[ T+~exp(--+)--t]mentioning
confidence: 99%
“…It was found that all the growth curves can be fitted reasonably well by the linear-parabolic equation. In the case of low oxygen partial pressure [14] and pyrogenic steam oxidation at high temperature [ 151, the linear rate constant may take a negative value. Fig.…”
Section: Determination Of Rate Constantsmentioning
confidence: 99%